The Hypothesis on the Prediction of Treatment Response with Buspirone Augmentation along with Serotonergic Antidepressant in Patients with Major Depressive Disorder Using Loudness Dependence of Auditory Evoked Potentials: Two Cases and Review of the Literature for Evidence - Park, Young-Min (Psychiatry Investig, 2020)
Some studies have shown that augmenting buspirone with antidepressant has similar efficacy as the combination with two antidepressants in patients with major depressive disorder (MDD). Some researchers assume that the antidepressant boosting effect of buspirone is revealed under a poop-out state, which means a phenomenon where some patients having an initial response to an antidepressant may worsen or not improve any more even though they continue treatment because of serotonin depletion. Loudness dependence of auditory evoked potential (LDAEP) is a reliable marker of central serotonergic activity, and is inversely correlated with central serotonergic activity. Thus LDAEP will be a biological marker for prediction of treatment response with buspirone augmentation with SSRI because it can measure central serotonergic activity such as serotonin depletion. Two cases will be introduced and the literature evidence about whether LDAEP can predict the treatment response of buspirone augmentation in patients with MDD will be reviewed.